Analisis Keterampilan Berbicara Siswa melalui Kegiatan Storytelling pada Pembelajaran Bahasa Indonesia SMP Kelas VIII - Hamriani; Ririn Sabriadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze students' speaking skills through storytelling activities in Indonesian language learning for eighth-grade junior high school students. This research uses a qualitative approach with a descriptive method. The subjects of this study were eighth-grade students. Data were collected through observation, interviews, and documentation. The data analysis technique used the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results showed that students' speaking skills were in the good category. The confidence indicator obtained the highest score, while intonation still needs improvement. Storytelling activities were proven to improve students' ability to speak fluently, use proper pronunciation, and organize stories coherently. In addition, this activity also increased students' confidence and participation in the learning process. Therefore, storytelling can be an effective alternative learning strategy to improve students' speaking skills.